Men's Accounts of Passion Killings in the Namibian Context. Issue 21 (November 2020) - Duff, Simon; Nampweya, Mirjam; Tree, Jeremy
Intimate partner violence (IPV) is a global social problem, which may result in intimate partner homicide (IPH). Much of the research concerned with IPH is based in developed nations and as such this study explored men's explanations for IPH (known locally as "passion killing") in the Namibian context by interviewing 10 individuals who were convicted and sentenced for the murder of their female intimate partners. A semi-structured interview was conducted with the offenders and the resulting transcripts were analyzed by Interpretative Phenomenological Analysis. Findings confirmed and extended previous research stating that the intertwined influence of cultural beliefs and attitudes, external influences, as well as lack of emotional control and problem-solving skills, influence IPH. However, the study discovered that culture-specific factors, such as witchcraft, also play a role in some IPH cases in Namibia. The findings suggest approaches to work with young men and perpetrators to reduce their rate of initially committing IPH or repeating it. Furthermore, understanding cross-cultural differences may help in developing appropriate, culturally specific, programs aimed at reducing and/or preventing IPH.